Mesial-Temporal Epileptic Ripples Correlate With Verbal Memory Impairment - Bruder, Jonas Christian; Wagner, Kathrin; Lachner-Piza, Daniel; Klotz, Kerstin Alexandra; Schulze-Bonhage, Andreas; Jacobs, Julia (Frontiers in Neurology, 2022)
Rationale: High frequency oscillations (HFO; ripples = 80-200, fast ripples 200-500 Hz) are promising epileptic biomarkers in epilepsy patients. However, especially in temporal epilepsies differentiation of epileptic and physiological HFO activity still remains a challenge. Physiological sleep-spindle-ripple formations are known to play a role in slow-wave-sleep memory consolidation. This study aimed to find out if higher rates of mesial-temporal spindle-ripples correlate with a good memory performance in epilepsy patients and if surgical removal of spindle-ripple generating brain tissue correlates with a decline of memory performance. In contrast, we hypothesized that higher rates of overall ripples or ripples associated with interictal epileptic spikes correlate with poor memory performance. Methods: Epilepsy patients that were implanted with electrodes in mesial-temporal structures, neuropsychological memory testing and subsequent epilepsy surgery were included. Ripples and epileptic spikes were automatically detected in intracranial EEG and sleep-spindles in scalp-EEG. Coupling of ripples to spindles was automatically analyzed. Mesial-temporal spindle-ripple rates in the speech-dominant-hemisphere (left in all patients) were correlated with verbal memory test results, whereas ripple rates in the non-speech-dominant hemisphere were correlated with non-verbal memory test performance, using Spearman correlation). Results: Intracranial EEG and memory test results from 25 patients could be included. All ripple rates were significantly higher in seizure onset zone channels (p<0.001). Patients with pre-surgical verbal memory impairment had significantly higher overall ripple rates in left mesial-temporal channels than patients with intact verbal memory (p = 0.039). Spearman correlations showed highly significant negative correlations of the pre-surgical verbal memory performance with left mesial-temporal spike associated ripples (rs= - 0.458; p= 0.007) and overall ripples (rs = - 0.475; p= 0.006). All three ripple-types in right-sided mesial-temporal channels did not correlate with pre-surgical nonverbal memory. No correlation for the difference of post- and pre-surgical memory and pre-surgical spindle-ripple rates was seen in patients with left-sided temporal or mesial-temporal surgery. Discussion: This study fails to establish a clear link between memory performance and spindle ripples. This highly suggests that spindle-ripples are only a small portion of physiological ripples contributing to memory performance.